An Assessment of Mobile Device Internet Services on Customer Perceived Value and Loyalty - Tai, Wern Shin Valerie (2009)
The objective of this study is to explore the effect of a complementary mobile and internet service offering around mobile devices on customer perceived value and consumer loyalty, as well as investigate if perceived value can predict consumer loyalty. Gender differences were also explored in both perceived value and loyalty.